2021
DOI: 10.1186/s12891-021-04088-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intra-articular calcaneal fractures: surgical treatment of 114 consecutive cases at a maximum care trauma center

Abstract: Background The aim of this retrospective monocentric study was to investigate the outcomes of surgically treated intra-articular calcaneus fractures in a maximum care trauma center. Methods One hundred forty patients who had undergone surgery for intra-articular calcaneal fractures between 2002 and 2013 were included. One hundred fourteen cases with 129 fractures were eligible to participate in the study of which 80 were available for a clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Finally, the patient's preference should be taken into account, and if they are hesitant about surgery or prefer non-operative treatment, this should be respected and discussed with their physician. [19]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the patient's preference should be taken into account, and if they are hesitant about surgery or prefer non-operative treatment, this should be respected and discussed with their physician. [19]…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the usual complications of any fracture fixation calcaneum is notorious for high incidence of skin complications and sab talar arthritis. 11 Studies have revealed a 70-100% incidence of subtalar arthritis in the long term follow up. [9][10][11] Some authors resort to subtalar fusion due to counter this dreaded complication.…”
Section: Discussionmentioning
confidence: 99%
“…11 Studies have revealed a 70-100% incidence of subtalar arthritis in the long term follow up. [9][10][11] Some authors resort to subtalar fusion due to counter this dreaded complication. 12 Our study concluded no significant difference between the two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Problems related to the subtalar joint have been reported, especially in publications on the EL approach (24). In a large-series study with a mean follow-up of 91 months, the rate of subtalar arthritis was found to be 77%, and it was reported that fusion was required in 18% of them (25). In the EL approach, it is necessary to wait for the foot edema to regress and skin lines to appear to avoid complications related to the surgical area.…”
Section: Discussionmentioning
confidence: 99%